Post‐mortem tissue donation programs as platforms to accelerate cancer research - Matthew Dankner; Badia Issa‐Chergui; Nathaniel Bouganim (Wiley, 2020)
Abstract Given recent advances in the treatment of cancer, patients are surviving longer but frequently develop treatment‐resistant and inoperable metastases. Biomedical research has advanced to the stage where in‐depth study of these lesions is feasible, with the goal of further refining our understanding of metastatic dissemination, therapeutic resistance and inoperable tumors. However, there is a lack of tissue specimens derived from multiple metastatic sites within the same patient that would permit the study of these processes. Furthermore, patients with rapidly progressing or metastatic disease are rarely candidates for surgery, making those most in need of innovation and discovery extremely difficult to study. For this reason, post‐mortem tissue donation programs are an approach that is quickly gaining traction in the cancer research community. Herein, we discuss what post‐mortem tissue donation entails, attitudes towards these procedures, and highlight important studies already utilizing these resources. In addition, we propose future directions for use of this tissue that can directly improve clinical management of advanced cancer patients.